Circular RNA circBNC2 inhibits tumorigenesis by modulating ferroptosis and acts as a nanotherapeutic target in prostate cancer - Xiang Pan; Kailai Chen; Wei Gao; Meiqi Xu; Fanlong Meng; Mengyuan Wu; Zi Qi Wang; Yun Qi Li; Wanhai Xu; Manjie Zhang; Yakun Luo (Molecular Cancer)
Abstract Background Metastasis is a leading cause of cancer-related death in castration-resistant prostate cancer (CRPC) patients. Circular RNAs (circRNAs) have emerged as key regulators of the metastasis of various cancers. However, the functional effects and regulatory mechanisms of circRNAs in metastatic CRPC (mCRPC) remain largely unknown. Methods The expression of circBNC2 in prostate cancer (PCa), CRPC and neuroendocrine prostate cancer (NEPC) tissues was analyzed through bioinformatics analysis. Functional assays, including cell proliferation, migration, invasion and ferroptosis, were conducted in vitro and in vivo. The interactions between circBNC2, miR-4298, and ACSL6 were explored via luciferase reporter assays, RNA immunoprecipitation, and western blotting analysis. In addition, for the first time in PCa, we developed novel nanobowls (NBs) loaded with docetaxel (DTX) and circBNC2 (Dc-NBs) and evaluated the antitumor efficacy of Dc-NBs in a photothermal therapy (PTT) strategy. Results We identified a novel tumor-suppressive circRNA, circBNC2, in human PCa, CRPC and NEPC samples via bioinformatic analysis. CircBNC2 expression was significantly downregulated in PCa tissues and PCa cell lines. Functional assays demonstrated that circBNC2 inhibited PCa cell proliferation and migration both in vitro and in vivo. Mechanistically, circBNC2 acted as a sponge for miR-4298, and ACSL6 was identified as a direct target of the circBNC2/miR-4298 axis. Moreover, we demonstrated that ACSL6 is essential for mediating circBNC2-regulated ferroptosis in PCa cells. More importantly, we demonstrated the nanodelivery of Dc-NBs, which exhibited significant antitumor effects in both subcutaneous and metastatic PCa models. Conclusion This study revealed the tumor-suppressive role of circBNC2 in mCRPC by driving ferroptosis via the circBNC2/miR-4298/ACSL6 axis. Additionally, we developed an efficient and safe PTT strategy based on a nanodelivery system that codelivers circBNC2 and DTX, highlighting its potential as a novel therapeutic approach for mCRPC.